Seasonal activity of insects trapped in stored wheat in Kansas and stored rice in Texas - Sellner, Matthew J. (Kansas State University, 2013)
Knowing the factors that influence the distribution patterns, establishment and persistence of stored product insects aids in the development of a more effective pest management program in grain storage structures. This research focuses mainly on the insect communities of stored wheat and stored rice in two different geographical locations, their temporal relationships and the most important or abundant species within that community. Stored wheat was sampled for one season in Manhattan, KS and for rice stored in Beaumont, TX was sampled for two seasons. Hairy fungus beetle, Typhaea stercorea (Coleoptera: Mycetophagidae) was one of the most abundant species and was present in every bin of either wheat or rice and appeared to move into and out of the grain mass. In wheat bin, Indianmeal moth, Plodia interpunctella (Lepidoptera: Pyralidae) was a predominant species captured in the bin headspace, but was not frequently recovered in the grain mass. Headspace temperatures tended to be warmer than grain temperatures and outside temperatures. Other major insects recovered in wheat bin included the following groups or species: Anthicidae, Lathridiidae, Cryptolestes, foreign grain beetle Ahasverus advena (Coleoptera: Silvanidae), sawtoothed grain beetle Oryzaephilus surinamensis (Coleoptera: Silvanidae), red flour beetle Tribolium castaneum (Coleoptera: Tenebrionidae), smalleyed flour beetle (Coleoptera: Tenebrionoidea) and minute pirate bug Xylocoris favipes (Hemiptera: Anthocoridae). In rice bins, the predominate species were hairy fungus beetle, foreign grain beetle and Angoumois grain moth Sitotroga cerealella (Lepidoptera: Gelechiidae). Angoumois grain moth was one of the most abundant species in rice, and was captured in the headspace as well as below the grain surface. Rice bins varied considerably in the relative abundance of different species between bins within a season and between seasons. Foreign grain beetle and hairy fungus beetle were especially variable among bins. Two species of weevil (Coleoptera: Curculionidae) that are not grain pests, the sugar cane rootstock weevil, Apinocis deplanata and rice water weevil, Lissorhoptrus oryzophilus (Coleoptera: Curculionidae), were present in high numbers in rice bins from September-December 2009.
Keywords: Entomology; Stored rice insects and temperature; Stored wheat insects and temperature; Entomology (0353)